The relationship between reading skills and fine motor abilities in younger school-aged children - Buha, Nataša; Banković, Slobodan; Gligorović, Milica (Specijalna edukacija i rehabilitacija, 2023)
The relationship between reading skills and fine motor abilities in younger school-age children Abstract Introduction. The role of motor skills in reading seems counter-intuitive, and thus it has played a minor role in studies on predictors of reading skills. The results of some studies indicate that the connection between motor skills and reading is present and that it depends on the examined motor component. Objective. The aim of this research was to determine the relation between visuomotor coordination and visuomotor integration with reading skills in younger school-age students. Methods. The sample included 103 participants aged 9 to 11 years. A Likert-type scale with four descriptors covering the most common types of problems during reading was used to evaluate reading skills. Fine motor skills were assessed with the subtests of the Acadia Test of Developmental Abilities - Visuomotor Coordination and Sequencing and Figure Copying. Intelligence, working memory, and inhibitory control were selected as covariates. Intelligence was assessed by Raven's Progressive Matrices, working memory by the Digit Span Backward task, and inhibitory control by the Go/NoGo task. Results. Hierarchical regression analysis showed that visuomotor coordination and working memory are independent predictors of reading skills. Visuomotor coordination explains 5.2% of the variance after removing the influence of intelligence and basic executive functions. A statistically significant relationship between visuomotor integration and reading skills was not found, so visuomotor integration was not considered a predictor in further analysis. Conclusion. When considering the importance of fine motor skills, it is necessary to analyze its individual components, because the results of this, as well as previous studies, indicate that not all aspects of fine motor skills are equally important factors in the development of reading skills. In the context of preventing difficulties in learning to read, it would be desirable to apply activities that would stimulate the development of fine motor skills and working memory from preschool age.
Keywords: reading skills; visuomotor coordination; visuomotor integration; executive functions; intelligence